2021
DOI: 10.1029/2021jb021673
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Foreshocks Revealed by an Earthquake Forecasting Method Based on Precursory Swarm Activity

Abstract: We have developed an empirical earthquake forecast method, Maeda's method, based on the statistical features of precursory seismic swarm activity, that is foreshocks, which sometimes appear before a mainshock, and issuing an alert of a mainshock occurrence within a certain period of time. In this study, we investigated the effectiveness of earthquake forecast of Maeda's method by applying it to seismicity under various tectonic environments of Japan such as regions characterized by interplate seismic activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…These recent observations are consistent with the inference made by Nishikawa and Ide (2018). Maeda and Hirose (2016) and Hirose et al (2021) systematically surveyed foreshock activity (M j 5 or greater) of M j ≥ 6 earthquakes in the Japan Trench from 1961 to 2010. They identified areas of pronounced foreshock activity far offshore in the Japan Trench (the orange shaded areas in Fig.…”
Section: Repeating Earthquakes Earthquake Swarms and Foreshocks Befor...supporting
confidence: 88%
See 3 more Smart Citations
“…These recent observations are consistent with the inference made by Nishikawa and Ide (2018). Maeda and Hirose (2016) and Hirose et al (2021) systematically surveyed foreshock activity (M j 5 or greater) of M j ≥ 6 earthquakes in the Japan Trench from 1961 to 2010. They identified areas of pronounced foreshock activity far offshore in the Japan Trench (the orange shaded areas in Fig.…”
Section: Repeating Earthquakes Earthquake Swarms and Foreshocks Befor...supporting
confidence: 88%
“…These results suggest that the foreshock activity in the Japan Trench cannot be explained by earthquake-to-earthquake triggering and that transient aseismic phenomena such as slow earthquakes may be involved in the triggering of the foreshocks. Moreover, Hirose et al (2021) found that foreshock activity in the northern Japan Trench had been synchronized with the 3-year periodic SSEs reported by Uchida et al (2016) (the far offshore black square in Fig. 7a) and suggested that the periodic SSEs had excited the foreshock activity.…”
Section: Repeating Earthquakes Earthquake Swarms and Foreshocks Befor...mentioning
confidence: 59%
See 2 more Smart Citations
“…In the Japan Trench, shallow slow slip is known to have preceded the 2011 M w 9.0 Tohoku earthquake (Ito et al, 2013). Hirose et al (2021) suggested that episodic SSEs along the Japan Trench excite foreshock activity based on analysis of precursory swarm activity. Therefore, it is also important to investigate the relationship between slow and ordinary earthquakes, as it may contribute to our understanding of the nucleation process of major earthquakes.…”
mentioning
confidence: 99%